Discovery of butyrylcholinesterase inhibitors among derivatives of azaphenothiazines. (February 2015) - Lodarski, Krzysztof; Jończyk, Jakub; Guzior, Natalia; Bajda, Marek; Gładysz, Joanna; Walczyk, Joanna; Jeleń, Małgorzata; Morak-Młodawska, Beata; Pluta, Krystian; Malawska, Barbara
Abstract The study presents the discovery of novel butyrylcholinesterase (BuChE) inhibitors among derivatives of azaphenothiazines by application of in silico and in vitro screening methods. From an in-house library of compounds, 143 heterocyclic molecules derived from the azaphenothiazine scaffold were chosen for virtual screening. Based on results of the docking procedure, 15 compounds were identified as exhibiting the best fit for the two screening complexes (ligand – AChE and ligand – BuChE). Five compounds displayed moderate AChE and good BuChE inhibitory activity at screening concentrations of 10 µM. The IC50 values for active BuChE inhibitors were in the 11.8–122.2 nM range. Three of the most active inhibitors are tetra- or pentacyclic derivatives of azaphenothiazines with the same N-methyl-2-piperidinethyl substituent.